Il valore dei report degli analisti finanziari nella quotazione delle piccole e medie imprese italiane - Musetti, Cristina (Piccola Impresa / Small Business, 2014)
The case study conducts a survey on the effects of investment recommendations contained in 1.015 financial analyst’s reports on stock prices of 29 SMEs, characterized by limited capitalization and admitted to listing on the MTA between 2003 and 2013. The effects were examined through an Event Study that studies the Cumulative Abnormal Returns associated with different event windows around the report date, the publication date of the reports. The analysis’s results show that these effects exist and vary across sub-sample and with respect to different recommendation’s categories.